The Protection of Women Refugees based on the Perspective of ASEAN Law: The Case of Rohingya Women Refugees - Soeparna, Intan (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
AbstractThe conflict of Rohingya has triggered human rights issues, including the ones that involve women refugees. Female Rohingya Refugees are facing the risks of sexual violence, abduction, trafficking, and prostitution. This situation indicates an urgent call for the realization of refugee protection, including the protection of women refugees according to ASEAN Law. ASEAN has made important institutional statements concerning the protection of womenâs human rights and the prevention of the violence against woman in its Human Right Law Regime. ASEAN also has made a statement to the Security Council on Women, Peace, and Security to address sexual violence in the conflicts that requires the tackling on the root-cause of the humanitarian disaster faced by Rohingya women refugees. However, the refugees policies of some ASEAN members, such as Malaysia, Indonesia, and Thailand, indicate less commitment to protect refugees. The fact gives impacts to women refugees. This article attempts to analyze the ASEAN role to protect Rohingya women refugees based on ASEAN legal commitment, including the ASEAN Regime of Human Rights. The purpose of the study is to imply the ASEAN legal commitment on the protection of womenâs right and to improve protection for women refugees, especially the Rohingya refugees. Â AbstrakÂ Konflik Rohingya menimbulkan berbagai bentuk masalah hak asasi manusia, terutama untuk pengungsi perempuan. Perempuan beresiko terhadap kekesaran seksual, perdagangan manusia dan prostitusi. Situasi ini menunjukan pentingnya merealisasikan perlindungan pengungsi termasuk pengungsi perempuan berdasarkan Hukum ASEAN, karena ASEAN sendiri telah membuat pernyataan penting berkaitan dengan perlindungan hak perempuan dan pencegahan kejahatan terhadap perempuan yang diatur dalam rejim hukum hak asasi manusia di ASEAN. ASEAN juga membuat pernyataan pada Dewan Keamanan PBB mengenai Perempuan, Perdamaian dan Keamanan bahwa ASEAN akan memperhatikan penyelesaian kejahatan seksual terhadap perempuan dalam situasi konflik dengan mensyaratkan penyelesaian akar permasalahan yang menimbulkan bencana kemanusiaan yang dihadapi oleh pengungsi perempuan Rohingya. Akan tetapi beberapa negara ASEAN (seperti Malaysia, Indonesia dan Thailand) memiliki kebijakan sendiri dalam memperlakukan pengungsi yang menunjukan kurangnya komitmen dalam melindungi pengungsi yang berakibat pada pengungsi perempuan. Oleh karena itu, artikel ini akan menganalisa peran ASEAN dalam melindungi pengungsi perempuan Rohingya berdasarkan komitmen ASEAN. Tujuannya adalah untuk menerapkan komitmen ASEAN dalam melindungi hak perempuan dan meningkatkan perlindungan bagi pengungsi perempuan Rohingya.DOI: https://doi.org/10.22304/pjih.v5n2.a2Â